Recurrent infection triggered encephalopathy syndrome in a pediatric patient with RANBP2 mutation and severe acute respiratory syndrome coronavirus 2 infection - Jiaqi Li; Feng Huo; Shuo Wang; Yimu Fan; Jie Wu; Zhezhe Zhang; Shuangjun Liu; Quan Wang (Wiley, 2023)
ABSTRACT Introduction Acute necrotizing encephalopathy (ANE), a fatal subtype of infection‐triggered encephalopathy syndrome (ITES), can be triggered by many systemic infections. RANBP2 gene mutations were associated with recurrent ANE. Case presentation Here we report a 1‐year‐old girl with recurrent ITES and RANBP2 mutation. She was diagnosed with influenza‐associated encephalopathy and made a full recovery on the first episode. After severe acute respiratory syndrome coronavirus 2 infection, the patient presented with seizures and deteriorating mental status. Brain magnetic resonance imaging revealed necrotic lesions in bilateral thalami and pons. Methylprednisolone, immunoglobulin, and interleukin 6 inhibitors were administered. Her consciousness level was improved at discharge. Nineteen cases of 2019 coronavirus disease‐related ANE have been reported, of which 22.2% of patients died and 61.1% had neurologic disabilities. RANBP2 gene mutation was found in five patients, two of whom developed recurrent ITES. Conclusion Patients with RANBP2 mutations are at risk for recurrent ITES, may develop ANE, and have a poor prognosis after relapse.